LO002: Improving safety of patients in respiratory distress: identifying preventable adverse events related to care provided in the emergency department. (2nd June 2016) - Pretty, S.; Scaffidi Argentina, S.; Vaillancourt, C.; Perry, J.J.; Stiell, I.G.; Forster, A.; De Gorter, R.; Calder, L.A.
Abstract : Introduction: Patients with acute exacerbations of heart failure (HF) or chronic obstructive pulmonary disease (COPD) may be at high risk for preventable adverse events (AEs). Preventable AEs are ED care-associated complications due to medical error. Our objective was to identify and characterize preventable AEs among ED patients over 50 presenting with dyspnea from an acute exacerbation of HF or COPD; who were subsequently admitted or discharged.Methods: We conducted a multicentre health records review from six academic centers in Ontario and Alberta. We analysed health records for all prospectively enrolled patients who experienced flagged outcomes: relapse to ED within 14 days requiring admission; admission to a monitored unit (AMU), cardiac care unit(CCU), or intensive care unit(ICU); intubation(ETI); non-invasive ventilation(NIV); diagnosis of acute myocardial infarction(AMI); or death within 30 days. Using a validated approach, an ED physician analyzed case summaries for flagged outcomes that were associated with ED care, designated as AEs. Preventable AEs had contributing errors in diagnosis, management, procedure, medications or unsafe disposition decisions. We analyzed these data using thematic coding and descriptive statistics.Results: Of 2, 515 patients enrolled (1, 100 HF and 1, 415 COPD), 210 patients experienced flagged outcomes, 47.1% of which were female, 64.3% had HF and the remaining COPD. The majority (86.2%) of flagged outcomes were related to underlying disease, but 13.8% of cases met criteria for AE and all were deemed preventable. Of the identified AEs, 72.4% returned to the ED and required admission to hospital; 17.2% were admitted to ICU, CCU, or AMU; 6.9% of patients died; 3.4% were intubated; 3.4% had a diagnosis of AMI and 0% required NIV. We found 75.8% of preventable AEs resulted from a management error (eg. not prescribing steroids on discharge for moderate COPD exacerbation); 31.0% from an unsafe disposition decision and 10.3% of AEs resulted from diagnostic error.Conclusion: Patients with acute exacerbations of HF and COPD are at high risk of preventable AEs directly related to care provided in the ED. Management and disposition decisions were a concerning source of error and should compel and focus future quality improvement efforts.